Drivers of foliar 15N trends in southern China over the last century. (19th June 2022) - Tang, Songbo; Liu, Jianfeng; Gilliam, Frank S.; Hietz, Peter; Wang, Zhiheng; Lu, Xiankai; Zeng, Feiyan; Wen, Dazhi; Hou, Enqing; Lai, Yuan; Fang, Yunting; Tu, Ying; et al.
Abstract: Foliar stable nitrogen (N) isotopes (δ 15 N) generally reflect N availability to plants and have been used to infer about changes thereof. However, previous studies of temporal trends in foliar δ 15 N have ignored the influence of confounding factors, leading to uncertainties on its indication to N availability. In this study, we measured foliar δ 15 N of 1811 herbarium specimens from 12 plant species collected in southern China forests from 1920 to 2010. We explored how changes in atmospheric CO2, N deposition and global warming have affected foliar δ 15 N and N concentrations ([N]) and identified whether N availability decreased in southern China. Across all species, foliar δ 15 N significantly decreased by 0.82‰ over the study period. However, foliar [N] did not decrease significantly, implying N homeostasis in forest trees in the region. The spatiotemporal patterns of foliar δ 15 N were explained by mean annual temperature (MAT), atmospheric CO2 ( P CO 2 ), atmospheric N deposition, and foliar [N]. The spatiotemporal trends of foliar [N] were explained by MAT, temperature seasonality, P CO 2, and N deposition. N deposition within the rates from 5.3 to 12.6 kg N ha −1  year −1 substantially contributed to the temporal decline in foliar δ 15 N. The decline in foliar δ 15 N was not accompanied by changes in foliar [N] and therefore does not necessarily reflect a decline in N availability. This is important to understand changes in N availability, which is essential to validate and parameterize biogeochemical cycles of N. Abstract : Foliar nitrogen (N) isotope (δ 15 N) but not foliar N concentrations ([N]) of 12 species decreased significantly over the past 90 years in southern China's forests. CO2, mean annual temperature, temperature seasonality, and N deposition drive the spatiotemporal patterns of foliar δ 15 N and [N]. Rising CO2 concentrations and increasing atmospheric N deposition dominate the temporally significant decrease in foliar δ 15 N and non‐significant decrease in foliar [N] of 12 species in southern China's forests. This is important to understand changes in N availability, which is essential to validate and parameterize biogeochemical cycles of N.